Antioxidant capacity of capulin (Prunus serotina subsp. capuli (Cav). McVaugh) fruit at different stages of ripening - Guerra-Ramìrez, Diana; Hernández Rodríguez, Guillermina; Espinosa- Solares, Teodoro; Perez-Lopez, Artemio; Salgado-Escobar, Irma (Ecosistemas y Recursos Agropecuarios, 2019)
Abstract. – Prunus serotina is a specie that grows wild or under cultivated conditions in several regions of America, and which has attracted considerable attention as a potential source of antioxidants. The study aimed to evaluate the concentration changes in compounds that contribute to the antioxidant capacity in capulín (Prunus serotina) fruits during the ripening process in order to define the time when the maximum concentration is reached. Antioxidant capacity was evaluated by spectroscopic methods. A completely randomized simple factor design was used for the statistical analysis. It was found that the content of total phenols and flavonoids decreased significantly at S3 (93 DAA) stage of ripening. Total anthocyanins increased significantly to 1.4 . The antioxidant capacity of the fruits had a maximum value of 63.7 at S3 stage of ripening (93 DAA). The results indicated that antioxidant capacity of the fruits is higher before reaching the characteristic purplish coloration, which is an indicator for consumption.